The functional instrumental test of flexion-extension motion in the radiocarpal joint: reference parameters - Dmitry V. Skvortsov; Danila A. Lobunko; Galina Е. Ivanova (Клиническая практика)
BACKGROUND: The stroke represents a significant medical-social problem due to its high morbidity and mortality with a tendency towards increasing the overall occurrence rates. A total 80% of the patients show persisting impaired functions of the upper limb. The current approaches, such as Clinical scales and Questionnaires, are being criticized for subjectivity and insufficient precision. It is necessary to develop an instrumental method for evaluating the functions of the upper limb, the method that is applicable in the clinical settings. AIM: To develop a functional test for the objective diagnostics of the wrist joint functions, applicable in the clinical settings. METHODS: A functional test was proposed for evaluating the biomechanics of the radiocarpal joint by means of using the inertial sensors. The research sample was a group of 15 healthy volunteers (5 males and 10 females aged from 23 to 33 years), not having any joint diseases or neurological disorders. The research was carried out within a period of one year (2022–2023). The primary endpoint was the determination of the amplitude, the time and the motion trajectory in the wrist joint when performing two tests - the “Wrist-0” and “Wrist-flex”. An assessment was done of the duration of the motion cycle, of the motion maximal amplitude and phase. RESULTS: The evaluation of the upper limb functions using the clinical scales (ARAT, FMA-UE, MRC) has demonstrated, that the parameters correspond to the ones in healthy individuals. When using the “Wrist-0” test, the motion amplitude was significantly lower than in the «Wrist-flex» test (p 0.05). No statistically significant differences were found in the motion amplitude between the right and left limbs determined using both tests (p 0.05). The maximal flexion phase for the “Wrist-0” tests occurs significantly earlier than for the “Wrist-flex” test for the right hand (p 0.05). The duration of the motion cycle did not significantly differ between the tests for the right hand (p 0.05) and was significantly higher for the “Wrist-flex” test in the left hand (p 0.05). CONCLUSION: A set of reference values was established for the functional tests. Insignificant differences were reported for the functions of the right and left radiocarpal joints. The test proposed requires insignificant time for its implementation and it can be used for objective diagnostics of the radiocarpal joint functions in patients.